2011
DOI: 10.1016/j.neuroscience.2011.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic nerve injury induces functional pro-nociceptive chemokine receptors in bladder-associated primary afferent neurons in the rat

Abstract: Visceral sensory afferents during disease or following injury often produce vague, diffuse body sensations and pain referred to somatic targets. Alternatively, injury due to trauma or disease of somatic nerve targets can also lead to referred pain in visceral targets via a somatovisceral reflex. Both phenomenons are thought to be due to convergence of visceral and somatic afferents within the spinal cord. To investigate a potential peripheral influence for referred pain in visceral targets following somatic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…laparotomy) can prime spinal microglia activation and subsequent LPS induced allodynia for as long as two weeks (Hains et al, 2010). More direct implications for IC/BPS symptoms have been demonstrated in an animal study that found a demyelination injury to the sciatic nerve increased the sensitivity of bladder-associated sensory neurons to chemokines and increased the frequency of micturition (Foster et al, 2011). …”
Section: 1 Discussionmentioning
confidence: 99%
“…laparotomy) can prime spinal microglia activation and subsequent LPS induced allodynia for as long as two weeks (Hains et al, 2010). More direct implications for IC/BPS symptoms have been demonstrated in an animal study that found a demyelination injury to the sciatic nerve increased the sensitivity of bladder-associated sensory neurons to chemokines and increased the frequency of micturition (Foster et al, 2011). …”
Section: 1 Discussionmentioning
confidence: 99%
“…By assessing [Ca 2+ ] i in DRG cells acutely isolated from LPC-treated rats in vitro, the number of DRG cells responding to CXCL12 increased following PLC administration. In another study, sciatic nerve injury induced by LPC increased the frequency of micturition and caused visceral pain hypersensitivity (Foster et al, 2011). It was found that CXCL12 increased [Ca 2+ ] i in somatic-and bladder-associated DRG neurons that were isolated from these PLC-treated animals.…”
Section: Cxcl12/cxcr4 Axis and Sciatic Nerve Injurymentioning
confidence: 95%
“…55 Since then LPC has been shown to cause demyelination in other central nervous system regions 56 as well as exhibiting demyelinating properties when applied to the peripheral nervous system. 57,58 In the context of CNS remyelination, LPC-induced spinal cord lesions still appear be the model of choice as the unidirectional path of axons in the spinal cord makes it easy to assess myelination and axon numbers by microscopy. Upon LPC injection, measurable demyelination can be seen within hours.…”
Section: A Paradigm Shift For Ms Therapeutics: Promoting Myelin Repairmentioning
confidence: 99%